SUSCEPTIBILITY PATTERN OF PREVOTELLA AND PORPHYROMONAS SPECIES FROM PATIENTS WITH ODONTOGENIC INFECTIONS IN LAGOS UNIVERSITY EACHING HOSPITAL TO AMOXICILLIN - CHUKWU EMELDA E M. SC; NWAOKORIE FRANCISCA O.PH. D.; UMEIZUDIKE KEHINDE A.FMCDS; KOLAWOLE MOSUMOLA.M. SC.; AGU REUBEN C.B. SC; ADESIDA SOLAYIDE A.PH. D.; COKER AKITOYE O. PH. D. (International Journal of Pharma and Bio Sciences, 2013)
Gram negative anaerobes are associated with periodontal inflammation leading to destruction of the periodontal ligament, supportive bone and subsequent tooth loss. This study was designed to characterize Prevotella and Porphromonas species from patients with odontogenic infections and evaluate their susceptibility pattern to amoxicillin a drug empirically administered in Nigerian dental clinics. Isolates were presumptively identified as Prevotella and Porphyromonas species by conventional cultural and biochemical analysis. Antimicrobial susceptibility pattern of the isolates to amoxicillin was determined by agar dilution method. Prevotella and Porphyromonas species showed susceptibility of 80% and 94% to amoxicillin respectively. Prevotella and Porphyromonas sp. resistant to amoxicillin are involved in oral infections in our population. Correct identification of these species and their corresponding susceptibility pattern will be of public health importance in selecting antibiotics for therapy in order to achieve better treatment outcomes.